Pengaruh Penggunaan Alat Bantu Pillbox Terhadap Tingkat Kepatuhan Minum Obat Dan Keberhasilan Terapi Pada Pasien Hipertensi Dengan komplikasi Gagal Jantung di RSU Nirwana Banjarbaru - Wati, Helmina; Restiana Rusida, Esty; Nurhaliza , Siti (Universitas Borneo Lestari, 2025)
Hypertension is recognised as a primary risk factor for the development of heart failure. Hypertension exerts an increased workload on the heart, thereby impeding its capacity to circulate blood throughout the body. The treatment of hypertension necessitates adherence to regular medication in order to regulate blood pressure and mitigate the risk of organ damage. The objective of this study is to ascertain the discrepancy in medication adherence levels subsequent to the provision of a pillbox device in comparison to patients who did not receive the pillbox device. Additionally, the study seeks to examine the correlation between adherence levels and blood pressure reduction. This study was a prospective pre-experimental study conducted from April to June 2022, involving 76 patients divided into two groups: the treatment group (given a pillbox) and the control group, each consisting of 38 patients. The analysis of the data was conducted utilising the SPSS software, employing the Mann-Whitney U test and the chi-square test. The findings demonstrated that 29 patients (76.31%) in the treatment group exhibited adherence to medication, in contrast to 10 patients (26.31%) in the control group. The mean blood pressure measurements in the treatment group before and after the intervention were 160/95 mmHg and 142/88 mmHg, respectively, compared to the control group, which had measurements of 151/86 mmHg and 144/79 mmHg before and after the intervention. Conclusion: A significant discrepancy in medication adherence was observed between patients who utilised the pillbox and those who did not (p-value = 0.000), and a substantial association was identified between medication adherence and blood pressure reduction following the administration of the pillbox (p-value = 0.001).